Clarithromycin Attenuates Left Ventricular Remodeling and Dysfunction after Pressure Overload in Mice - Yamada, Risako; Suzuki, Jun-Ichi; Ogawa, Masahito; Watanabe, Ryo; Isobe, Mitsuaki (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2012)
Background: Left ventricular (LV) hypertrophy is a natural adaption of the heart to pressure overloading and results in life-threatening heart failure. Matrix metalloproteinase (MMP) activity is upregulated in hearts with LV hypertrophy and its activation is the main cause of change in the LV wall. Clarithromycin (CAM), a major macrolide antibiotic, has various biologic effects including MMP regulation. However, little is known about the effect of CAM on LV hypertrophy. Methods and Results: To clarify the role of CAM on LV hypertrophy, we used the transverse aortic constriction (TAC) model. The mice were randomly assigned into three groups; (a) CAM administration with TAC (CAM-treated group, n=10); (b) vehicle administration with TAC (non-treated group, n=10); (c) vehicle administration with sham-operation (control group, n=10). M-mode echocardiograms showed that LV end-diastolic posterior wall (LVPWd) thickness increased progressively from week 1 to 3 after TAC in the non-treated group. However, it was attenuated in the CAMtreated group. Furthermore, heart to body weight ratio increased in the non-treated group (15.8±1.7%); this increase was negated by CAM administration (10.2±1.4%). Histpathologically, LV wall thickness increased in the non-treated group (18.0±4.0%); this increase was also negated in the CAM-treated group (-8.5±3.5%). Real-time RT-PCR demonstrated that CAM treatment tended to suppress MMP-9 and elevate TIMP-2 mRNA levels compared to the non-treated group. Conclusion: CAM attenuates the progression of LV hypertrophy via MMP suppression after pressure overload in mice. It might be a basic solution for LV hypertrophy.
Keywords: transverse aortic constriction